STRATEGI KOMUNIKASI KOMISI PEMILIHAN UMUM PROVINSI RIAU DALAM MENIGKATKAN PARTISIPASI MAHASISWA DI KOTA PEKANBARU PADA PEMILIHAN GUBERNUR RIAU 2018 - Firdaus, Muhammad; A’raaf, Bilhaqi Amjada (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The communications strategy is that concrete acts of the series of activity communication. General election commission has mission change thinking patterns students not only function as vote ( an object ), but be someone not only function as choose, but also to contribute helps to spread, voicing, both in his group and in its place (an subject ). Election commission Governor Riau 2018, increase participation voters cub from the election of the Governor Riau 2013 before and this increase cannot be separated from the communications strategy run. Hence, the purpose of research is how the communications strategy general election commission riau in increase the participation of students voters novice in Pekanbaru at an election Governor Riau 2018.The methodology used in research is the methodology descriptive qualitative. Data collection techniques used is interview, observation and documentation. But the subject of specified using purposive techniques, that is consisting of seven people from general election commission Riau, two people from the care General Election and Democracy Riau and ten student voters novice, including ten students were, two of the Community Care and Democracy Provincial Elections Riau. The analysis technique used data analysis reverence of miles and huberman. Examination technique the validity of data driving participation, and triangulation source.The result of this research showed that the communications strategy did Riau Province General Election by the commission to increase the participation of students as voters novice making a three programs: “goes to campus“, smart house general election, and the Community Care General Election and Democracy Riau Province, one in which the program run well seiringan third, but in the process of changing the way people think of an object into the subject of examination, done in stages, first starting from “goes to campus” by which the opening is knowledge and stated mean the purpose, smart house election to get to know deeper into questions of general election commission, and the Community Care General Election and Democracy as a medium college students to join and voicing his opinion and helping General Election Commission of Riau to increase the participation of good they and the community.Keyword :Communication Strategy, The General Electiion Commission Province of Riau, Collage Student